2015
DOI: 10.1371/journal.pone.0131859
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Dietary Fat Content Rapidly Alters the Mouse Plasma Coagulation Profile without Affecting Relative Transcript Levels of Coagulation Factors

Abstract: BackgroundObesity is associated with a hypercoagulable state and increased risk for thrombotic cardiovascular events.ObjectiveEstablish the onset and reversibility of the hypercoagulable state during the development and regression of nutritionally-induced obesity in mice, and its relation to transcriptional changes and clearance rates of coagulation factors as well as its relation to changes in metabolic and inflammatory parameters.MethodsMale C57BL/6J mice were fed a low fat (10% kcal as fat; LFD) or high fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…This is consistent with previous studies showing that HFD-fed C57BL/6J mice exhibited significantly shorter aPTT and PT than lean mice fed a standard diet 44 . HFD-feeding of C57BL/6J mice results in higher thrombus weight in a thrombosis model 45 and to increased plasma levels of coagulation factors FII, FVII, FVIII, FIX, FXI and FXII 46 . This may be part of the mechanisms underlying the enhanced activity of the individual coagulation factors observed in the present study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous studies showing that HFD-fed C57BL/6J mice exhibited significantly shorter aPTT and PT than lean mice fed a standard diet 44 . HFD-feeding of C57BL/6J mice results in higher thrombus weight in a thrombosis model 45 and to increased plasma levels of coagulation factors FII, FVII, FVIII, FIX, FXI and FXII 46 . This may be part of the mechanisms underlying the enhanced activity of the individual coagulation factors observed in the present study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Nishimura et al showed that in obese and HFD-fed mice, there is increased platelet-leukocyte interaction and tethering, and blocking the endothelial inflammatory surface marker ICAM1 can normalize these effects [ 113 ]. Cleuren et al showed that HFD feeding leads to a rapid increase of circulating blood clotting factors, and the source of these is the activated endothelium rather than the liver, which is the main source of circulating clotting factors [ 114 ]. In addition, studies interfering with basic activators of blood clotting or platelet ligands have been shown to ameliorate HFD-induced inflammation and insulin resistance, such as mice lacking PAR2, a key target of tissue factor/factor VII mediated coagulation, or mice lacking the PSGL1, a main ligand for P-selectin, a surface protein exposed on activated platelets [ 115 , 116 ].…”
Section: Inflammation As the Common Denominator For Cardiovascular DImentioning
confidence: 99%
“…HFD induces atherosclerosis (18) by enhancing dyslipidemia and macrophage infiltration in the aorta (18). HFD also alters the coagulation profiles and promotes hypercoagulopathy, by increasing plasma levels of endogenous thrombin and procoagulant factors (e.g., FII, FVII, FVIII, and FXII), or decreased fibrinolysis (19). Hypercoagulability is common in HIV/SIV infections and may contribute to residual immune activation and inflammation (20) even in individuals with ART suppression (2,3).…”
Section: Resultsmentioning
confidence: 99%